STATUS RESISTENSI NYAMUK Anopheles sp.TERHADAP INSEKTISIDA MALATHION DI KOTA KUPANG - Julianty Almet; Diana A. Wuri; Antin Y. N. Widi; Edwin K. Ndawa Lu (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The aim of this study is to investigate the insectidace resistance of Anopheles sp. to malathion 0.8% in Kota Lama and Maulafa districts. This study used the sample approximately 650 of Anopheles sp. The collected mosquitoes are inserted into the maintenance cage to identify and ensure that the mosquito is truly Anopheles sp. The test was done by using impregnanted paper malathion 0.8% .Amount of 25 mosquitoes were caught using an aspirator and put into a collector tube which had been coated with 0.8% impregnated paper malathion , while other 25 mosquitoes were put into a green tube and had no insecticide paper. The test results were obtained by counting the knocked down mosquitoes every 15 minutes during 2 hours of insecticide exposure and continued for 24 hours of holding time. The test was repeated for 3 times. The results showed that Anopheles sp. in Kota Lama and Maulafa districts, were resistant to Malathion insecticides 0.8% with the percentage of death mosquitoes (Kota Lama: 4,35-28% ; Maulafa: 8-12,5%)(< 90%). So it has a high level of resistance.